Identification and functional characterization of rare SHANK2 variants in schizophrenia - Slavil Peykov; Simone Berkel; Michael Schoen; Kerstin Weiß; Franziska Degenhardt; Jana Strohmaier; B Weiss; Christian Proepper; Gerhard Schratt; Markus M. Nöthen; Tobias M. Boeckers; Marcella Rietschel; et al. (2015)
Recent genetic data on schizophrenia (SCZ) have suggested that proteins of the postsynaptic density of excitatory synapses have a role in its etiology. Mutations in the three SHANK genes encoding for postsynaptic scaffolding proteins have been shown to represent risk factors for autism spectrum disorders and other neurodevelopmental disorders. To address if SHANK2 variants are associated with SCZ, we sequenced SHANK2 in 481 patients and 659 unaffected individuals. We identified a significant increase in the number of rare (minor allele frequency<1%) SHANK2 missense variants in SCZ individuals (6.9%) compared with controls (3.9%, P=0.039). Four out of fifteen non-synonymous variants identified in the SCZ cohort (S610Y, R958S, P1119T and A1731S) were selected for functional analysis. Overexpression and knockdown-rescue experiments were carried out in cultured primary hippocampal neurons with a major focus on the analysis of morphological changes. Furthermore, the effect on actin polymerization in fibroblast cell lines was investigated. All four variants revealed functional impairment to various degrees, as a consequence of alterations in spine volume and clustering at synapses and an overall loss of presynaptic contacts. The A1731S variant was identified in four unrelated SCZ patients (0.83%) but not in any of the sequenced controls and public databases (P=4.6 × 10−5). Patients with the A1731S variant share an early prodromal phase with an insidious onset of psychiatric symptoms. A1731S overexpression strongly decreased the SHANK2-Bassoon-positive synapse number and diminished the F/G-actin ratio. Our results strongly suggest a causative role of rare SHANK2 variants in SCZ and underline the contribution of SHANK2 gene mutations in a variety of neuropsychiatric disorders.